Melatonin prevents cisplatin‐induced primordial follicle loss via suppression of PTEN/AKT/FOXO3a pathway activation in the mouse ovary. Issue 3 (2nd March 2016) - Jang, Hoon; Lee, Ok‐Hee; Lee, Youngeun; Yoon, Hyemin; Chang, Eun Mi; Park, Miseon; Lee, Jeong‐Woong; Hong, Kwonho; Kim, Jung Oh; Kim, Nam Keun; Ko, Jung Jae; Lee, Dong Ryul; et al.
Abstract: Premature ovarian failure (POF) is a major side effect of chemotherapy in young cancer patients. To develop pharmaceutical agents for preserving fertility, it is necessary to understand the mechanisms responsible for chemotherapy‐induced follicle loss. Here, we show that treatment with cisplatin, a widely used anticancer drug, depleted the dormant follicle pool in mouse ovaries by excessive activation of the primordial follicles, without inducing follicular apoptosis. Moreover, we show that co‐treatment with the antioxidant melatonin prevented cisplatin‐induced disruption of the follicle reserve. We quantified the various stages of growing follicles, including primordial, primary, secondary, and antral, to demonstrate that cisplatin treatment alone significantly decreased, whereas melatonin co‐treatment preserved, the number of primordial follicles in the ovary. Importantly, analysis of the PTEN/AKT/FOXO3a pathway demonstrated that melatonin significantly decreased the cisplatin‐mediated inhibitory phosphorylation of PTEN, a key negative regulator of dormant follicle activation. Moreover, melatonin prevented the cisplatin‐induced activating phosphorylation of AKT, GSK3β, and FOXO3a, all of which trigger follicle activation. Additionally, we show that melatonin inhibited the cisplatin‐induced inhibitory phosphorylation and nuclear export of FOXO3a, which is required in the nucleus to maintain dormancy of the primordial follicles. These findings demonstrate that melatonin attenuates cisplatin‐induced follicle loss by preventing the phosphorylation of PTEN/AKT/FOXO3a pathway members; thus, melatonin is a potential therapeutic agent for ovarian protection and fertility preservation during chemotherapy in female cancer patients.